Ecoremediation for implementation of environmental objective - Vovk Korže, Ana; Vrhovšek, Danijel (Journal for Geography, 2007)
The environmental aims are published in the operative programmes, directives and other EU strategic documents and international agreements. They could be found in National programme of environmental protection as well. They are directed to achieving well environmental conditions and the due time for each environmental goal is set as well. In the paper we want to show the positive influence of ecoremediation to achieving the environmental aims. As an example we started from the list of environmental goals for waters. The need of water protection is mentioned in the Water framework directive and in the Waters act.